Determination of the local structure of CsBi4−xPbxTe6 (x = 0, 0.5) by X-ray absorption spectroscopy. Issue 36 (26th August 2016) - Wakita, Takanori; Paris, Eugenio; Mizokawa, Takashi; Hacisalihoǧlu, Muammer Yasin; Terashima, Kensei; Okazaki, Hiroyuki; Proux, Olivier; Kieffer, Isabelle; Lahera, Eric; Del Net, William; Olivi, Luca; Takano, Yoshihiko; et al.
Abstract : We have studied the local structure and valence electronic unoccupied states of CsBi4 Te6 and CsBi3.5 Pb0.5 Te6 ( T c ∼ 3 K) by EXAFS and XANES measurements. Abstract : We have studied the local structure and valence electronic unoccupied states of thermoelectric CsBi4 Te6 and superconducting CsBi3.5 Pb0.5 Te6 ( T c ∼ 3 K) by extended X-ray absorption fine structure (EXAFS) and X-ray absorption near edge structure (XANES) measurements. The Bi-L3 edge EXAFS reveals wide Bi–Te distance distribution for both compounds indicating complex atomic arrangements in the studied system. The mean square relative displacements (MSRDs) of the Bi–Te bond distances appear largely increased in Pb substituted system due to larger overall local disorder, however, one of the Bi–Te bonds shows a reduced disorder. On the other hand, the Bi-L3 edge XANES is hardly affected by Pb substitution while the Te-L1 edge XANES reveals increased density of unoccupied Te 5p states. This suggests that the carriers introduced by the Pb substitution in CsBi4− x Pb x Te6 preferentially goes on Te sites. Similarly, the Cs-L3 edge XANES also shows small changes due to Pb-substitution and reduced local disorder indicated by the reduced width of the Cs-L3 edge white line. We have also shown that the X-ray photoemission spectroscopy (XPS) measurements on various electronic core levels are in a qualitative agreement with the XANES results. These findings are consistent with carrier doping and a reduced disorder in one direction to be likely factors to drive the thermoelectric CsBi4 Te6 into a bulk superconductor by Pb-substitution in CsBi4− x Pb x Te6 .